Thermal radiation control from hot graphene electrons coupled to a photonic crystal nanocavity - Ren-Jye Shiue (Nature Portfolio, 2019)
Efficient control of thermal radiation is at the core of device design for a variety of applications. Here, the authors demonstrate a high-temperature thermal emitter with selective emission from a graphene-silicon photonic crystal nanocavity.